The Role Of Village-Owned Enterprises In Increasing Green Economic Development In Villages - Mulastih, Listiana Sri; Rohmah , Umdah Aulia; Hardayu, Audisty Prana; Ningsih, Tri Widyastuti; Syofya, Heppi (Journal Of Human And Education (JAHE), 2024)
This article comes from the author's service in the villages of Bulak and Bandar Baru for 1 month in these villages. This dedication began with the writer/devotee's sense of concern for villages that have great potential to be invaded by radicalism. This program is also a priority for BNPT and the Government of the Republic of Indonesia. "National preparedness as part of prevention is mandated by law, and we will implement this in village strengthening activities later, because if villages are ready, there is no room for terror groups to invite young people to become part of them," said the Commissioner General. Pol. Boy Rafli Amar. The results in this article show 1). One of the places where radicalism has the potential to enter is rural areas due to education, literacy and so on. 2). The teaching of religious moderation is a teaching that upholds the values of tolerance, four, and so on by relaxing the rules in religion. 3). Therefore, the writer/devotee decided to carry out education on religious moderation in order to counter radicalism in rural areas. This program is also in line with the BNPT and Indonesian Government programs.